E-PAYMENT INFORMATION SYSTEM AT FAMILYMART BRANCH PT. AT INDONESIA - Ramdhani, Eka Chandra; Kusuma, Mochamad Surya; Haryadi, Eko; Asep, Asep; Sapitri, Juniarti Eka (Journal of Information System, Applied, Management, Accounting and Research, 2024)
The study aims to design e-payment information systems at FamilyMart, one of AT Indonesia's branches, in response to business dynamics and technological developments in the retail sector. By initiating a need analysis step through a deep understanding of FamilyMart's retail business processes and customer preferences, the study explores the potential for implementation of e-betalings technology to improve operational efficiency and provide a more comfortable shopping experience. Through direct observation methods, interviews with stakeholders, and literature, the study attempts to identify key features of e-payment systems, integrate them with existing cashier systems, as well as highlight necessary security aspects. In the deeper scope, the research includes conceptual modelling, analysis of software needs, and development of waterfall models as early stages of implementation. The development focuses on security aspects and integration with existing information technology infrastructure. The results of this research are expected to provide a strategic foundation for PT AT Indonesia in the face of an increasingly digitalized business era.